Disruption in the balance between apolipoprotein A‐I and mast cell chymase in chronic hypersensitivity pneumonitis - Inoue, Yukihisa (Immun Inflamm Dis, 2020)
BACKGROUND: Apolipoprotein A‐I (apoA‐I) has an antifibrotic effect in idiopathic pulmonary fibrosis. Although pulmonary fibrosis is associated with poor prognosis of patients with hypersensitivity pneumonitis (HP), little is known regarding the role of apoA‐I in the pathogenesis of HP. METHODS: Two‐dimensional electrophoresis, immunoblotting, and enzyme‐linked immunosorbent assays were performed for the identification and quantification of apoA‐I in bronchoalveolar lavage fluid (BALF) from patients with acute and chronic HP. To investigate the degradation of apoA‐I, apoA‐I was incubated with BALF. Moreover, the role of apoA‐I in TGF‐β1‐induced epithelial–mesenchymal transition of A549 cells was examined. RESULTS: The concentration of apoA‐I in the BALF was significantly lower in chronic HP (n = 56) compared with acute HP (n = 31). The expression level of apoA‐I was also low in the lung tissues of chronic HP. ApoA‐I was degraded by BALF from HP patients. The number of chymase‐positive mast cells in the alveolar parenchyma was inversely correlated with apoA‐I levels in the BALF of chronic HP patients. In vitro experiment using A549 cells, untreated apoA‐I inhibited TGF‐β1‐induced epithelial–mesenchymal transition, although this trend was not observed in the chymase‐treated apoA‐I. CONCLUSIONS: A decrease of apoA‐I was associated with the pathogenesis of chronic HP in terms of pulmonary fibrosis and mast cell chymase attenuated the protective effect of apoA‐I against pulmonary fibrosis. Furthermore, apoA‐I could be a crucial molecule associated with lung fibrogenesis of HP.